Penerapan Kurikulum 2013 Dalam Meningkatkan Prestasi Belajar Siswa Kelas VIII PK4 Di MTs N 1 Surakarta Tahun Pelajaran 2015/2016 - Rahmawati, Ayu Yuliana Heri; , Drs. Mahasri Shohabiya (2017)
Curriculum 2013 is now the applied curriculum in Indonesia education, it is established to enhance the previous curriculum that focuses on active student. Learning achievement is the results achieved by students after process of teaching and learning. The achievement is usually indicated by the numerical score as the learning outcomes of students reported to the parents. To reach learning achievement is not easy. It is affected by various factors, both internal and external factors. In formal education, the school is the institution that is very important in determining the success of student learning, and therefore the school establishes several programs to meet the needs of participant students and parents, in order to achieve the determined objectives. Several programs at the school are very influential on the result of differences in learning achievement of the participant students. By this background, the purpose of this study is to describe the implementation of the curriculum in 2013 to improve student achievement in grade VIII PK 4 at MTs N 1 Surakarta. This research is done at MTs N 1 Surakarta and so it is included in the field research. The research subjects are the students of grade VIII taking special program. In collecting data, this research uses interview, observation, and documentation methods. Moreover, in analyzing data, this research uses descriptive qualitative approach. The result shows that student achievements of the research subjects increase, with the classroom average 6,88. Their achievements are caused by several factors, including: environmental factors, motivation, time, classroom atmosphere, as well as learning interest of student school facilities and infrastructures.